Wear and corrosion interactions on titanium in oral environment : literature review - Souza, Júlio C. M. (2015)
The oral cavity is a complex environment where corrosive substances from dietary, human saliva, and oral biofilms may accumulate in retentive areas of dental implant systems and prostheses promoting corrosion at their surfaces. Additionally, during mastication, micromovements may occur between prosthetic joints causing a relative motion between contacting surfaces, leading to wear. Both processes (wear and corrosion) result in a bio-tribocorrosion system once that occurs in contact with biological tissues and fluids. This review paper is focused on the aspects related to the corrosion and wear behavior of titanium-based structures in the oral environment. Furthermore, the clinical relevance of the oral environment is focused on the harmful effect that acidic substances and biofilms, formed in human saliva, may have on titanium surfaces. In fact, a progressive degradation of titanium by wear and corrosion (tribocorrosion) mechanisms can take place affecting the performance of titanium-based implant and prostheses. Also, the formation of wear debris and metallic ions due to the tribocorrosion phenomena can become toxic for human tissues. This review gathers knowledge from areas like materials sciences, microbiology, and dentistry contributing to a better understanding of bio-tribocorrosion processes in the oral environment.